Rhein restores the sensitivity of mcr-1 carrying multidrug-resistant Escherichia coli to colistin - Wang, Nannan; Yang, Dan; Cao, Lijuan; Zhao, Xinghong; Song, Xu; Zhou, Xun; Jia, Renyong; Zou, Yuanfeng; Li, Lixia; Lv, Cheng; Jing, Bo; Yin, Zhongqiong (Frontiers in Microbiology, 2025)
The emergence of the colistin resistance gene mcr-1 has resulted in a significant reduction in the clinical efficacy of colistin against infections caused by multidrug-resistant Gram-negative pathogens. A cost-effective approach for restoring the efficacy of antibiotics is to formulate synergistic antibiotic combinations with natural compounds that target the resistance of multidrug-resistant bacteria. In this study, we have demonstrated that rhein can effectively restore the sensitivity of mcr-1-positive Escherichia coli to colistin, both in vitro and in vivo. Mechanism studies have demonstrated that rhein primarily damages bacterial cell membranes, disrupts proton motive force, and generates excessive reactive oxygen species, and down-regulates the mcr-1 gene in E. coli. Compared to monotherapy, the combination of rhein and colistin greatly increased the survival rate of E. coli infected mice and significantly reduced the bacterial load in the viscera of the mice. Our results confirm that rhein serves as a promising adjuvant to colistin and, in combination with colistin, provides a viable approach to combat infections caused by colistin resistant E. coli.